Prophylactic and therapeutic parotidectomy for secondary neoplasms of the parotid gland - Ant, Ayca; Toprak, Felat; Kılıç, Caner; Özlügedik, Samet; Duran, Arzubetül; Tunçcan, Tuncay (The European Research Journal, 2020)
Objectives: The aim of this study was to review the demographic and clinicopathological findings of the patients who underwent prophylactic or therapeutic parotidectomy due to the secondary neoplasm of the parotid gland (SNP), the outcomes of the patients with SNP and to provide a perspective to the parotid and neck approach in head and neck skin cancer cases.Methods: The clinical data of 178 patients who underwent parotidectomydue to neoplasm in the Department of Otorhinolaryngology, Head and Neck Surgery of a tertiary referral center from 2012 to 2017 were reviewed.Results: Among 178 patients, twenty-two (12.4%) patients were found to underwentprophylactic or therapeutic parotidectomy due to SNP. Six of these patients had pathologically positive parotid metastases (therapeutic parotidectomy). The median age of six patients was 67 years (ranging from 2 to 83 years). Five patients were male and one was female. The most common indication of parotidectomy (prophylactic and therapeutic) and pathology of parotid mass due to SNP and Cutaneous Squamous Cell Carcinoma (SCC) (36.3% and 50%, respectively).Conclusions: Owing to rapidly progressive feature and high morbidity, close observation of parotid in case of metastasis is crucial for recurrent SCC of the face and scalp.